2020
DOI: 10.1038/s41598-020-69787-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlative study of epigenetic regulation of tumor microenvironment in spindle cell melanomas and cutaneous malignant peripheral nerve sheath tumors

Abstract: the tumor microenvironment (tMe) plays critical roles in tumor growth and progression, however key regulators of gene expression in the tMe of cutaneous malignant peripheral nerve sheath tumor (c-MpnSt) and spindle cell melanoma (ScM) have not been well elucidated. Herein, we investigate the epigenetic regulation of promoters and gene bodies and their effect on the TME composition of C-MPNSTs and SCMs. A cohort of 30 patients was analyzed using differential gene expression (DGE) and gene set enrichment analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Chromatin accessibility regulates cellular transcriptional states by affecting the binding of transcription factors (TFs). To identify the key transcription factors linking the chromatin accessibility with transcriptional characteristics of TAMs, we performed sequence‐based motif analysis with HOMER v4.9 29 and found that the binding sites of CTCF which was a high rank of TFs by motif analysis were significantly enriched in hyper‐accessible regions (Figure 1E) and some previously published articles revealed that CTCF critically controls gene expression in macrophages via epigenetic regulation, 30,31 indicating the upregulation of CTCF activity in TAMs. CTCF was a heritable component of an epigenetic system regulating the interplay between DNA methylation, high chromatin structure, and lineage‐specific gene expression, so we were interested in studying the function of CTCF and locating the key CTCF binding sites in TAMs.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin accessibility regulates cellular transcriptional states by affecting the binding of transcription factors (TFs). To identify the key transcription factors linking the chromatin accessibility with transcriptional characteristics of TAMs, we performed sequence‐based motif analysis with HOMER v4.9 29 and found that the binding sites of CTCF which was a high rank of TFs by motif analysis were significantly enriched in hyper‐accessible regions (Figure 1E) and some previously published articles revealed that CTCF critically controls gene expression in macrophages via epigenetic regulation, 30,31 indicating the upregulation of CTCF activity in TAMs. CTCF was a heritable component of an epigenetic system regulating the interplay between DNA methylation, high chromatin structure, and lineage‐specific gene expression, so we were interested in studying the function of CTCF and locating the key CTCF binding sites in TAMs.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, because epigenetic mechanisms are crucial for different clinical outcomes of MPNST patients (129), the results of this study are promising and hold great potential for deeper investigation.…”
Section: Nerve Sheath Tumor Regulation By Calebin Amentioning
confidence: 85%
“…Cell-type composition of the tumour microenvironment (TME) consisting of cancer, immune and stromal cells, is crucial for defining clinically relevant tumour subtypes or drug development in immunotherapy [27,28]. DNAm data-based TME deconvolution has been done by using array-based data [29,30] and provided valuable insights in various cancer studies [31,32]. However, sequencing-based TME methylation deconvolution still has not been extensively applied.…”
Section: Discussionmentioning
confidence: 99%